Financial Inclusion and Economic Growth in Nigeria - Babajide, Abiola A.; Adegboye, Folasade B.; Omankhanlen, Alexander E. (International Journal of Economics and Financial Issues, 2015)
Financial development is not simply a result of economic growth; it is also the driver of economic growth. Financial inclusion (FI), a feature of fi nancial development, is a process that marks improvement in quantity, quality, and effi ciency of fi nancial intermediary services. It generates local savings, which increase productive investments in local businesses. This paper investigated the impact of FI on economic growth in Nigeria. It aimed to highlight the determinants of FI and its impact on economic growth. Secondary data were sourced from world development indicators and ordinary least square regression model was used to analyze the data. The result shows that FI is a signifi cant determinant of the total factor of production, as well as capital per worker, which invariably determines the fi nal level of output in the economy. This study recommends that natural and economic resources should be adequately harnessed, as alternative means of revitalization and diversifi cation of Nigeria's oil-dependent monocultural economy. Keywords: Financial Inclusion; Economic Growth; Nigeria JEL Classifications: G21; O4